Chronic anti-inflammatory effect of bees’ honey on Freund’s Complete Adjuvant induced arthritis in rats - Weerakoon, W.A.S.S.; Perera, P.K.; Gunasekera, D.; Suresh, T.S. (Sri Lanka Journal of Indigenous Medicine (SLJIM), University of Colombo, 2020)
Bees’ honey has been used to treat in many diseases in traditional medicine. The usage of bees’ honey as a medicine is referred to in the most ancient Ayurveda medical records. Therefore, this study was design to evaluated the chronic anti-inflammatory effect of bees’ honey using adjuvant-induced arthritis in experimental rat model. Healthy male Wistar rats were randomly assigned into 4 groups (n=6 in each). Arthritis was induced by a single intra-dermal injection of Freund’s Complete Adjuvant (FCA) containing Mycobacterium butyricum suspension into a foot pad of the left hind paw of all groups of Wistar rats except healthy control group (Group I). Group II - arthritic rats were received distilled water. Group III-arthritic animals treated with a standard drug Celecoxib (5mg/kg) and Group IV- arthritic animals were received BH (4ml/kg). Following induction of arthritis, daily oral treatment was started on day 14 and continued up to day 28. Body weight, ankle joint thickness and foot pad thickness were measured in all animals using dial calliper on Day 0 and on Day 3,7,10,14,17,21,24 and 28 after the injection of adjuvant. Full blood count was tested on day 28. Induction of arthritis significantly increased FPT, AJT and loss of BW. Treatment with Bees’ honey and standard drug Celecoxib in the arthritic animals produced significant reductions respectively p<0.05, p<0.001 in FPT, AJT, WBC count, reducing erythema and oedema in the ankle joints and foot pad of the AIA rats and normalized BW. This study provided transitional medicinal evidence for BH used in the treatment of chronic inflammation in traditional medicine.
Keywords: Arthritis; Bees’ honey; Chronic antiinflammatory effect